Asuhan Keperawatan pada Tn. A dengan Gangguan Sistem Hematologi dan Imunologi : Dengue Haemoragic Fever di Ruang Dahlia RSUD Dr. Soeselo Kabupaten Tegal - Mulidah Nurul Hidayah; Tati Karyawati; Muhammad Silahudin; Yusriani Saleh Baso (Jurnal Anestesi, 2024)
The immunodeficiency system is a condition when the body's immunity is disrupted, so that it cannot fight infections and diseases. This type of disorder can make the body easily infected by viruses and bacteria. Then viruses and bacteria easily enter the body due to a decrease in the immune system, this triggers various kinds of disease problems, one of which is dengue hemorrhagic fever (DHF) (Nuryanti et al, 2022).